Microbial regulation of arsenopyrite oxidation and arsenic transformation in pyrrhotite-mediated interactions - Shuang Zhou; Yusi Qin; Zhiqi Chen; Zhenlei Cai; Yongjie Bu; Weijian Yu; Chenyang Zhang; Keyi Yang; Min Gan; Qingjun Guan (Bioresource Technology, 2027)

Surface-confined AlOxFy on thermal shock-generated α-Al2O3 for coke-resistant dehydrofluorination of 1,1-difluoroethane - Zhenxiang Li; Yongchao Zhao; Fengqing Hu; Zaizhe Cheng; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Ying Li; Wujian Zhang; Haodong Tang (Chemical Engineering Journal, 2026)

The acid polysaccharides extracted from Moringa leaf improve DSS-induced ulcerative colitis by targeting intestinal microbiota metabolism - Wen Lang; Xinyun Qin; Yizhe Dou; Keyi Nong; Ruixue Cao; Tingyu Chen; Wanyan Chen; Bin Zhang; Zheng Yang; Bowen Tian; Jijun Wang; Lianbin Li; et al. (Food Research International, 2026)

Comparative plastid genomics of five Ormosia species (fabaceae): insights into structural variation and morphological homoplasy - Shihong Zhang; Fengcheng Deng; Yixiong Zhao; Jiating Wang; Dipak Khadka; Jieyu Lin; Yuhua Hu; Keyi Fu; Lei Jiang; Mingxuan Zheng; Shi Shi (Plant Systematics and Evolution, 2026)

Soil-specific resilience of comammox and canonical ammonia oxidizers shapes drought-heat legacy effects on N2O emissions - Shuoshuo Wu; Zhenhua Liang; Keyi Zhang; Jun Li; Baowei Hu; Guixin Chu; Rui Tao (Environmental Research, 2026)

Highly efficient H2S absorption and conversion by cyclohexanone-enhanced ionic liquid composite systems - Xiankun Wu; Huiqin Xu; Keyi Huang; Wentao Zheng; Youting Wu; Xiaomin Zhang (Chemical Engineering Journal, 2026)

Ultra-fast degradation of sulfonamides by Fe/Cu-LDH functionalized biochar activated peroxymonosulfate: Interfacial catalysis driven multiple reactive oxygen species - Yongfei Ma; Keyi Li; Feifei Zhang; Zhaojun Nie; Shiyu Qin; Haiyang Liu; Yupeng Zhang; Jiayang Xu; Zulin Zhang; Peng Zhao; Hongen Liu (Chemical Engineering Journal, 2026)

Valorizing jackfruit shell into a hydrothermal liquid seed-priming agent for salinity-stressed crops - Tao Zhang; Yanping Zhu; Yongle Yu; Keyi Zhang; Pan Zhao; Xiaomeng Han; Weigang Wang; Shihu Shu; Dandan Ke; Xiuping Zhan; Xiaoshuang Han; Jiping Shi; et al. (Bioresource Technology Reports, 2026)

A multi-scale framework with machine learning for hydrogen transport properties in nuclear thermal propulsion - Keyi Li; Haochun Zhang; Ziyang Zhou; Ersheng You (Annals of Nuclear Energy, 2026)

ΔA146Ply exerts anti-triple-negative breast cancer effects by inducing ferroptosis via regulation of the CYP24A1-mediated calcitriol-vitamin D receptor pathway - Ye Yu; Zhengkun Zhang; Dingxue Wang; Xin Bai; Dan He; Xuxu Ji; Zhaoru Yin; Keyi Xu; Ji Liu; Jiaqiong Zou (Toxicology and Applied Pharmacology, 2026)

Distance-aware cooperative Kriging-assisted evolutionary algorithm for expensive many-objective optimization - Junhua Liu; Keyi Kou; Wei Zhang; Meng Wang; Mengnan Tian (Swarm and Evolutionary Computation, 2026)

Searching for potential biosignatures in impact-induced hydrothermal systems on Mars - Yuchun Wu; Yang Liu; Zengqian Hou; Keyi Li; Chaolin Zhang; Yongliao Zou (Science Bulletin, 2026)

Investigation on Patulin biotransformation in Zebrafish and its toxicological function evaluation - Shuang Li; Shubing Chen; Keyi Fang; Peng Zhu; Sijia Zhang; Shun Zhang; Ting Cai (Mycotoxin Research, 2026)

Lapatinib Induces Ferroptosis in Cardiomyocytes by Regulating ATF4/GPX4 - Yue Sun; Keyi Jiang; Dan Wang; Chunlei Li; Yuqing You; Long Chen; Wei Chang; Liwei Zhang; Hongqi Feng; Dandan Li; Yilan Li (Cardiovascular Toxicology, 2026)

Genetic Variants in EMT-Related lncRNAs Modulate the Risk of Colorectal Cancer in the Chinese Population - Simeng Gu; Zhaohui Zhang; Keyi Cheng; Aibuta Yeerken; Sangni Qian; Fanjia Guo; Mingjuan Jin; Kun Chen (Biochemical Genetics, 2026)

Spatiotemporal variability, driving factors, and potential human health risks of fluoride and nitrate in surface water and groundwater of a sandy desert lake basin, Northwest China - Xiangwei Li; Muhan Li; Shen Qu; Keyi Zhang; Yuanzhen Zhao; Ao Gao; Renpu Wang; Dongchao Huo; Zongbao Yue; Bowen Ye; Hongli Ma; Ping Miao; et al. (Journal of Environmental Sciences, 2026)

Measurement and prediction of water-energy-food-economy-ecology coupling coordination degree in Shandong Province, China - Chenjun Zhang; Man Li; Xiangyang Zhao; Yuze Wang; Keyi Ju (Ecological Modelling, 2026)

Impact of emission inventory uncertainty on secondary inorganic aerosol simulation over Beijing–Tianjin–Hebei region - Yulong Li; Xiao Tang; Keyi Chen; Lei Kong; Wei Feng; Tianming Lu; Kai Cao; Quan Zhang; Zifa Wang (Atmospheric Pollution Research, 2026)

Evaluation of Groundwater Origin, Quality, and Potential Health Risks in the Ordos Coal Mine Base, Northwest China: Insights from Geochemical and Isotopic Approaches - Jiaming Zhou; Keyi Zhang; Tenglin Deng; Zilong Liao; Bing Xu; Fei Gao; Quandong Lian; Jianghong Yan; Shen Qu (Mine Water and the Environment, 2026)

Vertical distribution pattern, preferred life strategies and environmental response of prokaryotic microbiome in the eastern tropical indian ocean - Jinfeng Wang; Wenbin Zhao; Shaodong Zhu; Keyi Huang; Yulin Zhang; Haojin Cheng; Qin Ma; Derui Song; Jiwen Liu; Xiao-Hua Zhang; Xiaolei Wang (Marine Environmental Research, 2026)

Ruthenium supported on grain-boundary-induced oxygen-vacancy-rich CeO2 for efficient ammonia decomposition - Jinghua Liu; Wujian Zhang; Junhan Yang; Yongchao Zhao; Jian Guan; Zhenxiang Li; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Chunshan Lu; Angjian Wu; et al. (Chemical Engineering Journal, 2026)

Molecular-weight-dependent effects of humic acid on hexavalent chromium accumulation and reduction in green microalgae - Li Luo; Keyi Zhou; Mawuli Dzakpasu; Kena Zhang; Tong Yang; Wenshan Guo; Huu Hao Ngo; Xiaochang C. Wang (Journal of Hazardous Materials, 2026)

Mechanistic insights into synergistic co-removal of Cr(VI) and Cu(II) by polyethyleneimine-chitosan/imidazolium-polysulfone composite beads from simulated electroplating rinse wastewater - Xiaojie Zhang; Keyi Liu; Zihan Zhang; Hong Peng; Yuefa Gong (Journal of Environmental Chemical Engineering, 2026)

Application of Bi2MoO6 materials in ammonia synthesis through photocatalytic nitrogen fixation - Ping Zhang; Xinyu Du; Keyi Chai; Jiaqi Guo; Lu Zhang; Xiaoping Su; Lianbiao Zhao (Journal of Environmental Chemical Engineering, 2026)

A plasticity-aware machine learning framework for genomic prediction and resource-efficient wheat breeding under multi-environment conditions - Lei Li; Cong Zhao; Huihui Li; Xi Tian; Jindong Liu; Duoxia Wang; Keyi Wang; Shuaipeng Fei; Guoliang Wan; Jianqi Zeng; Yachao Dong; Jixin Li; et al. (Computers and Electronics in Agriculture, 2026)

Multi-isotope coupling models for revealing sulfate source and migration associated with lacustrine groundwater discharge in a large mining area on the Loess Plateau - Zhengguang Zhang; Shen Qu; Xiangyang Liang; Zilong Liao; Yuanzhen Zhao; Keyi Zhang; Chenyu Wang; Fei Gao; Quandong Lian; Ruihong Yu (Process Safety and Environmental Protection, 2026)

Dual-modal antioxidant nanozyme hydrogel for protection against noise-induced hearing loss via attenuation of oxidative stress and NF-κB/MAPK signaling - Liang Xia; Ru Tang; Yi Chen; Ning Ma; Lili Xiao; Xiaoyan Chen; Xiaoyin Mao; Keyi Li; Yanmei Feng; Jingjing Liu; Amin Zhang (Chemical Engineering Journal, 2026)

Accurately tracking radial location dynamics of freeze-thaw front in tree stems under field conditions: a comprehensive model considering non-uniformity of stem water content distribution and electric-field attenuation of electromagnetic sensor - Yuxin Liu; Xiaofei Yan; Taisheng Du; Ricardo F. de Oliveira; Keyi Zhang; Qiang Cheng (Agricultural and Forest Meteorology, 2026)

Investigation of SNPs at NKCC Gene of Scylla paramamosain to Unveil the Low-Salinity Tolerance Phenotype - Chunyan Yin; Yanqing Ma; Zhiqiang Liu; Xueyang Wang; Keyi Ma; Wei Wang; Chunyan Ma; Fengying Zhang (Fishes, 2026)
The Na+/K+/2Cl− cotransporter (NKCC) gene encodes a critical membrane transporter involved in cellular ion homeostasis and plays a pivotal role in osmoregulation and salinity adaptation in aquatic organisms. This study identified and validated SNP markers in the NKCC gene associated with low-salinity tolerance in Scylla paramamosain. Four SNPs (g.196C>A, g.8374T>A, g.8385T>A and g.91143T>A) were screened and genotyped in low-salinity tolerant and intolerant groups. Association analysis revealed that mutant genotypes at all four sites were significantly enriched in the tolerant group (p

Assessing social equity and urban heat risks with machine learning of remote sensing imagery: A Pittsburgh case study - Zekun Li; Sri Ramana Saketh Vasanthawada; Keyi Chai; Linyue Luo; Xiao Xu; Ying Zhang; Kristen Kurland; Vivian Loftness (Sustainable Cities and Society, 2026)

Deciphering spatio-seasonal impacts of agricultural irrigation on water quality evolution and surface water-groundwater interaction in a large irrigation district, northwest China - Muhan Li; Keyi Zhang; Wei Bao; Shen Qu; Guanglei Yu; Yansong Bai; Xu Yang; Zeyuan Liu; Hongli Ma; Ping Miao; Fuyang Huang; Ruihong Yu (Journal of Hydrology, 2026)

UVB enhances SLC6A15-mediated phenylalanine transport to promote melanogenesis - Shu Zhou; Yujie Ouyang; Yibo Hu; Xixia Dai; Ling Jiang; Chuhan Fu; Yaqing Wen; Jiangfeng Huang; Keyi Zhang; Jing Chen; Qinghai Zeng (Journal of Photochemistry and Photobiology B: Biology, 2026)

Contrastive mechanisms of lacustrine groundwater discharge and associated pollutant fluxes into two typical inland lakes in Inner Mongolia, Northwest China - Yuanzhen Zhao; Xiaohui Ren; Shen Qu; Fu Liao; Keyi Zhang; Muhan Li; Juliang Wang; Ruihong Yu (Journal of Environmental Sciences, 2026)

Microbial community assembly and functional adaptation of urease-producing bacteria in oil reservoirs: Driven by phase heterogeneity and selective enrichment - Yanlong He; Keyi Liu; Tengda Huang; Weibo Wang; Xiaoqi Zhang; Lu Bai; Junxi Zhang; Hai Huang (Journal of Environmental Chemical Engineering, 2025)

Covalency modulated by Fe-F-Fe configuration and oxygen vacancy promotes dual mechanism for oxygen evolution reaction - Bo Feng; Keyi Lv; Ziyong Zhang; Nianwen Song; Ziyang Yan; Yuchao Zhang; Yanfei Wei; Xiaofei Yu; Lanlan Li; Xinghua Zhang; Xiaojing Yang; Zunming Lu; et al. (Chemical Engineering Journal, 2025)

From heterogeneity to prognosis: understanding the complexity of tertiary lymphoid structures in tumors - Yingying Wang; Dongyan Zhang; Xueping Huang; Guohao Wu; Chuanbao Wang; Jun Li; Song Wang; Xinmiao Xian; Bo Fu; Keyi Li (Molecular Biology Reports, 2025)

Shipowners’ responses to carbon tax: speed optimization using AIS data - Hailing Liu; Keyi Ju; Xiaozhuo Wei; Chenjun Zhang; Jianghang Zhou (Clean Technologies and Environmental Policy, 2025)

Emergence and genomic characterization of Vibrio parahaemolyticus serotype O10:K4 from seafood-linked diarrheal cases in Zhejiang, China (2016–2023) - Jiewen Huang; Zhen Zhang; Qingtian Li; Jiancai Chen; Lingling Mei; Xiaojuan Qi; Lili Chen; Junyan Zhang; Chao Lv; Min Li; Honghu Chen; Yanjun Zhang; et al. (Food Research International, 2025)

Mechanistic insights into Perfluorooctanoic acid (PFOA) and Perfluorooctane sulfonates (PFOS)-induced nitrification acceleration: Interkingdom collaboration of AOA-comammox in calcareous soils - Shuoshuo Wu; Keyi Zhang; Yuehang Zhu; Luo Zhang; Wangying Ding; Jun Li; Baowei Hu; Guixin Chu; Rui Tao (Journal of Hazardous Materials, 2025)

Selective enrichment of comammox over NOB Nitrospira on biofilm in low-oxygen integrated fixed-film activated sludge system - Yunlong Li; Jin Chen; Bowen Wang; Naif Abdullah Al-Dhabi; Zimin Chai; Keyi Zhang; Shujun Huang; Wangwang Tang; Maosheng Zheng (Journal of Environmental Chemical Engineering, 2025)

Environmental exposure to heavy metals and their potential impact on prostate cancer prognosis-related gene expression - Wei Song; Tao Zhang; Jianliang Ou; Jinliang Ni; Jiong Tang; Houliang Zhang; Haipeng Zhang; Guangchun Wang; Jun Chang; Bo Peng; Keyi Wang (Food and Chemical Toxicology, 2025)

Spatio-seasonal variability of source contributions to water quality in a large irrigation drainage lake basin based on the entropy weighted quality index, positive matrix factorization, and isotopic tracers - Keyi Zhang; Muhan Li; Shen Qu; Yuanzhen Zhao; Limin Duan; Xu Yang; Dingyi Li; Zilong Liao; Ruihong Yu (Environmental Pollution, 2025)

Imidazolium salt-functionalized Cu2O@SiO2 catalysts for integrated CO2 capture and electroreduction to multi-carbon products in acidic electrolytes - Hui Zhang; Shanshan Lou; Fan Yang; Keyi Fan; Zhengxin Gu; Wangbo Li; Yihe Chen; Yizhen Gan; Lushan Ma; Guoliang Wang; Hui Yang (Chemical Engineering Journal, 2025)

Foundation model-based apple ripeness and size estimation for selective harvesting - Keyi Zhu; Jiajia Li; Kaixiang Zhang; Chaaran Arunachalam; Siddhartha Bhattacharya; Renfu Lu; Zhaojian Li (Computers and Electronics in Agriculture, 2025)

A hydroxyl coumarin-chalcone-based fluorescent probe for sensing copper ions in plant and living cells - Keyi Li; Yan Huang; Yatong Sun; Yiping Zhang; Yan Zhang; Baosheng Ren; Duxia Cao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Four years of air exposure: Passive surface chemical engineering to improve the stability and photoluminescence performance of CsPbBr3 perovskite quantum dot glass - Yongmin Duan; Shugang Li; Keyi Gu; Zhaojing Kuang; Juan Du; Junjie Zhang (Chemical Engineering Journal, 2025)

Dipole-polarized Cu–Ni atomic interfaces for synergistic enhancement and steering of overall nitrogen photofixation - Longjian Li; Ping Zhang; Reyila Tuerhong; Yongchong Yu; Keyi Chai; Lianbiao Zhao; Xiaoping Su; Lijuan Han (Chemical Engineering Journal, 2025)

Legacy effects of three decades of past organic fertilization improve rice primary productivity via enhancing soil enzymatic and bacterial resistance under copper stress - Keyi Zhang; Wangying Ding; Shuoshuo Wu; Guixin Chu; Baowei Hu; Rui Tao (Journal of Soils and Sediments, 2025)

Application of a fluorescent probe exhibiting a large stokes shift after the precise detection of hydrazine in plants, foods and living cells - Yan Zhang; Yan Huang; Guiyi Yang; Haotian Xin; Keyi Li; Lei Wang; Shangcong Gu; Baosheng Ren; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2025)

Spatial variability of lacustrine groundwater discharge and pollutant fluxes in the sandy-land lake group basins: Influence from land use types - Shen Qu; Xiangwei Li; Ao Gao; Yuanzhen Zhao; Keyi Zhang; Yiwei Zhang; Dongchao Huo; Bowen Ye; Zongbao Yue; Renpu Wang; Hongli Ma; Ping Miao; et al. (Journal of Environmental Management, 2025)

Synergizing farmland reverting and energy substitution programs in Wolong through agent-based modelling and cost-efficiency analysis - Keyi Liu; Yufeng Chen; Liyan Xu; Xiao Zhang; Zilin Wang; Hailong Li; Yansheng Yang; Hong You; Dihua Li (Ecological Modelling, 2025)

Structural characteization and anti-colorectal cancer activity of a fucogalactan purified from Ganoderma tsugae - Xin Zhang; Shuai Liu; Keyi Wu; Lili Shu; Yu Li; Lanzhou Li; Di Wang (Carbohydrate Polymers, 2025)

Design of F doped sulfide bifunctional catalyst and investigation on the mechanism transformation of oxygen evolution reaction - Nianwen Song; Keyi Lv; Bo Feng; Ziyong Zhang; Xiangwen Tan; Yanfei Wei; Ziyang Yan; Yuchao Zhang; Xiaofei Yu; Lanlan Li; Xinghua Zhang; Xiaojing Yang; et al. (Chemical Engineering Journal, 2025)

OsPAD1, encoding a non-specific lipid transfer protein, is required for rice pollen aperture formation - Qiming Wang; Yunlu Tian; Keyi Chen; Shanshan Zhu; Yehui Xiong; Chaolong Wang; Xiaowen Yu; Wenting Bai; Hai Zheng; Shimin You; Yang Hu; Dekun Lei; et al. (Plant Molecular Biology, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

Gonadal expression profiles reveal the underlying mechanisms of temperature effects on sex determination in the large-scale loach (Paramisgurnus dabryanus) - Lei Zhang; Yutong Fang; Mijuan Shi; Keyi Ren; Xin Guan; Waqar Younas; Yingyin Cheng; Wanting Zhang; Yaping Wang; Xiao-Qin Xia (Animal Reproduction Science, 2025)

Enterovibrio qingdaonensis sp. nov. and Enterovibrio gelatinilyticus sp. nov., two marine bacteria isolated from surface seawater of Qingdao offshore - Keyi Huang; Yi Liu; Yan Wang; Pingping Zhang; Haojin Cheng; Jinfeng Wang; Wanjia Tong; Wang Xiaolei; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2025)

Development and evaluation of a dual-arm robotic apple harvesting system - Kyle Lammers; Kaixiang Zhang; Keyi Zhu; Pengyu Chu; Zhaojian Li; Renfu Lu (Computers and Electronics in Agriculture, 2024)

Preparation, separation, and identification of antioxidant peptides from protein hydrolysate of Polygonatum cyrtonema Hua - Yanyan Zhang; Shengjun Ma; Haixia Li; Peizi Liu; Keyi Chen; Wei Cai (Food Bioscience, 2024)

Convenient synthesis of granulated Li/Al-layered double hydroxides/chitosan composite adsorbents for lithium extraction from simulated brine with a high Mg2+/Li+ ratio - Liqin Zhao; Xiaojie Zhang; Keyi Liu; Xin Liu; Yuefa Gong; Hong Peng; Wei Qi (Chemical Engineering Journal, 2024)

Game changer for anaerobic fermentation of paper mulberry: Sucrose-loaded biochar enhancing microbial communities and lactic acid fermentation - Jingwen Cao; Hongzhang Zhou; Xuekai Wang; Yang Wang; Yu Li; Stephen Joseph; Xiaorong Wang; Mengyao Sun; Keyi Zhang; Yanli Lin; Gang Xu; Kuikui Ni; et al. (Bioresource Technology, 2024)

Decoding PTEN: from biological functions to signaling pathways in tumors - Xueping Huang; Dongyan Zhang; Di Zhang; Jianran Guo; Guohao Gu; Yingying Wang; Guohao Wu; Chuanbao Wang; Bo Fu; Keyi Li (Molecular Biology Reports, 2024)

Identification and characterization of autoallododecaploid barnyard grass (Echinochloa crus-galli L.) induced by in vitro colchicine treatment - Keyi Liu; Xiaoling Zhou; Wei Wang; Xiaoxiao Wu; Ziwei Zhao; Xiaolu Yang; Ziyi Feng; Pincang Lv; Jie Wang; Wangwen Zhu; Xianhua Zhang; Yuchi He; et al. (In Vitro Cellular & Developmental Biology - Plant, 2024)

Immobilization of Pb2+ and Cd2+ in water by sodium alginate magnet-biochar composite and LCA evaluation - Weiwen Dai; Kexin Lu; Juan Zhang; Shulian Wang; Keyi Liu; Huiqin Zhang (Journal of Water Process Engineering, 2024)

An infrared radiation-responsive high-entropy CoCaMgMnAlFe-LDHs for controllable hydrogen generation via NaBH4 hydrolysis: Utilization of steel slag and lithium-ion battery liquid waste - Qiaoqi Li; Fei Wang; Xiaoyan Liu; Wenhao Xu; Keyi Zhang; Siyuan Zhang; Pengfei Teng; Lili Zhang (Chemical Engineering Journal, 2024)

Realizing reasonable redistribution of platform capacity through valence structure optimization for low strain Na3MnZr(PO4)3 cathode material - Mengting Deng; Yulei Sui; Kexin Rao; Yian Wang; Wenbin Fei; Keyi Sun; Zonglin Yang; Xiaoping Zhang; Ling Wu (Chemical Engineering Journal, 2024)

Multi-isotopes (δD, δ18Owater, 87Sr/86Sr, δ34S and δ18Osulfate) as indicators for groundwater salinization genesis and evolution of a large agricultural drainage lake basin in Inner Mongolia, Northwest China - Shen Qu; Yuanzhen Zhao; Keyi Zhang; Juliang Wang; Muhan Li; Xu Yang; Xiaohui Ren; Yanling Hao; Ruihong Yu (Science of The Total Environment, 2024)

Near-infrared and multifunctional fluorescent probe enabled by cyanopyridine cyanine dye for bisulfite recognition and biological imaging - Shangcong Gu; Yan Huang; Xinxin Li; Haotian Xin; Haoran Mu; Yan Zhang; Keyi Li; Guiyi Yang; Songfang Zhao; Duxia Cao (Journal of Hazardous Materials, 2024)

Response of comammox Nitrospira clades A and B communities to long-term fertilization and rhizosphere effects and their relative contribution to nitrification in a subtropical paddy field of China - Rui Tao; Wangying Ding; Keyi Zhang; Yanyan Li; Jun Li; Baowei Hu; Guixin Chu (Journal of Environmental Management, 2024)

6:2 Cl-PFESA, a proposed safe alternative for PFOS, diminishes the gemcitabine effectiveness in the treatment of pancreatic cancer - Jiawei Hong; Keyi Du; Weichen Zhang; Junran Chen; Hangbiao Jin; Yuanchen Chen; Yifan Jiang; Hanxi Yu; Xiaoyu Weng; Shusen Zheng; Jun Yu; Linping Cao (Journal of Hazardous Materials, 2024)

A novel bimetallic-polyanion Na4Fe2.82Ni0.18(PO4)2P2O7 cathode with superior rate performance and long cycle-life for sodium-ion batteries - Wenbin Fei; Yian Wang; Xiaoping Zhang; Jiuxiang Zhang; Shengxing Lu; Kexin Rao; Keyi Sun; Mengting Deng; Yuxuan Liu; Qingqiang Li; Ling Wu; Yulei Sui (Chemical Engineering Journal, 2024)

The cooperative interaction of AOB and comammox clade A drives nitrification and N2O emissions in a long-term organic fertilized paddy soil - Keyi Zhang; Wangying Ding; Xiran Zhao; Jun Li; Guixin Chu; Rui Tao (Applied Soil Ecology, 2024)

High nutrient utilization and resorption efficiency promote bamboo expansion and invasion - Keyi Zuo; Lili Fan; Ziwu Guo; Le Zhang; Yiyang Duan; Jingrun Zhang; Shuanglin Chen; Hua Lin; Ruicai Hu (Journal of Environmental Management, 2024)

Recognition of autism spectrum disorder in children based on electroencephalogram network topology - Fali Li; Shu Zhang; Lin Jiang; Keyi Duan; Rui Feng; Yingli Zhang; Gao Zhang; Yangsong Zhang; Peiyang Li; Dezhong Yao; Jiang Xie; Wenming Xu; et al. (Cognitive Neurodynamics, 2024)

Core-shell nanoconfinement: Nanoreactors for directional electron migration in photothermal-assisted photocatalytic hydrogen production - Yu Shen; Yuxing Shi; Zhouze Chen; Shunhong Zhang; Keyi Chen; Xuefeng Luo; Feng Guo; Guangzhao Wang; Weilong Shi (Chemical Engineering Journal, 2024)

Combining microbiome and pseudotargeted metabolomics revealed the alleviative mechanism of Cupriavidus sp. WS2 on the cadmium toxicity in Vicia unijuga A.Br. - Xuefeng Yuan; Dandan Wu; Dingguo Zhang; Chunyu He; Zilong Wang; Wenqian Xu; Na Shou; Keyi Fu; Mingyuan Yue; Xin Zhang; Zunji Shi (Environmental Pollution, 2024)

Microplastics sequestered in the soil affect the turnover and stability of soil aggregates: A review - Tianhang Ju; Kai Yang; Lei Chang; Keyi Zhang; Xingyi Wang; Jialin Zhang; Bo Xu; Yuefen Li (Science of The Total Environment, 2023)

Large-scale surface water-groundwater origins and connectivity in the Ordos Basin, China: Insight from hydrogen and oxygen isotopes - Shen Qu; Chenyu Wang; Nuan Yang; Limin Duan; Ruihong Yu; Keyi Zhang; Muhan Li; Pengfei Sun (Environmental Research, 2023)

Effects of four diets on the metabolism of megalopa metamorphosis of the mud crab, Scylla paramamosain - Keyi Ma; Zhiqiang Liu; Guangde Qiao; Lingbo Ma; Fengying Zhang; Ming Zhao; Chunyan Ma; Wei Wang (Frontiers in Marine Science, 2023)
Dietary intake is an essential source of energy and nutrients, and plays an irreplaceable role in the breeding of S. paramamosain seedlings. In this study, live Artemia nauplii (LA), compound feeds (CF), frozen copepods (FC) and frozen adult Artemia (FA) were utilized as feed during the megalopa stage. To determine the impact that diet has on the metabolism of crablets that underwent metamorphosis from the megalopa stage, analyses of both metabolomics and fatty acid content were conducted. In the LC-MS-based metabolomics analysis, a total of 104, 205 and 83 significantly different metabolites (SDMs) were identified after being fed with FC, FA, and CF, respectively, as compared to the LA group. Furthermore, significant differences in KEGG compounds among the three comparisons exhibited similarity and were mainly associated with categories such as “Lipids”, “Hormones and transmitters”, and “Peptides”. The fatty acid content analysis indicated that the ΣMUFA was significantly higher in the LA and CF groups compared to the other two groups. In contrast, the highest level of ΣPUFA was found in the LA group. In addition, the CF group showed significantly higher expression levels of the fatty acid synthesis genes, FAS and ACC . Conversely, the expression level of the fatty acid decomposition-related gene CPT1 was the highest in the LA group. In comparison with the FA group, the expression level of FABP3 was significantly decreased in the LA and CF groups. In summary, there were significant differences observed in the metabolic profiles of crablets that metamorphosed from the megalopa under different diets. Our experimental results suggested that LA is more advantageous in the cultivation of the S. paramamosain megalopa compared to the other three diets. While it remains a diet that cannot be entirely substituted at present, LA has the potential to improve the culture performance of the S. paramamosain megalopa. The current study could provide valuable data into the development of artificial diets necessary for the future of the mud crab seedling breeding industry.

Chronic exposure to (2 R,6 R)-hydroxynorketamine induces developmental neurotoxicity in hESC-derived cerebral organoids - Zhulin Du; Zhenle Zang; Jing Luo; Tianyao Liu; Ling Yang; Yun Cai; Liuyongwei Wang; Dandan Zhang; Jinghui Zhao; Junwei Gao; Keyi Lv; Lian Wang; et al. (Journal of Hazardous Materials, 2023)

Motion behavior of non-Newtonian fluid-solid interaction foods - Yuhe Fan; Lixun Zhang; Canxing Zheng; Xingyuan Wang; Keyi Wang; Jinghui Zhu (Journal of Food Engineering, 2023)

Distributed spatial crowdsourcing based task allocation in Ocean Internet of Things - Hongtang Cao; Ying Guo; Fei Li; Keyi Zhang (Earth Science Informatics, 2023)

Suppression of ETI by PTI priming to balance plant growth and defense through an MPK3/MPK6-WRKYs-PP2Cs module - Dacheng Wang; Lirong Wei; Ting Liu; Jinbiao Ma; Keyi Huang; Huimin Guo; Yufen Huang; Lei Zhang; Jing Zhao; Kenichi Tsuda; Yiming Wang (Molecular Plant, 2023)

Physical activity can influence the relationship between ethylene oxide and risk of kidney stones: A cross-sectional study from the NHANES 2013–2016 - Hua Jiang; Keyi Wang; Heng Zhang; Bin Yang; Weipu Mao; Ming Chen; Shuigen Zhou (Environmental Science and Pollution Research, 2023)

Pharmacokinetic profile and sub-chronic toxicity of coenzyme Q10 loaded whey protein nanoparticles - Cuina Wang; Ru Zhao; Keyi He; Siyu Zhang; Alyssa H. Kemp; Mingruo Guo (Food Bioscience, 2023)

A spatiotemporal graph convolution-based model for daily runoff prediction in a river network with non-Euclidean topological structure - Liangkun Deng; Xiang Zhang; Shiyong Tao; Ye Zhao; Keyi Wu; Jie Liu (Stochastic Environmental Research and Risk Assessment, 2023)

Correction to: Relationship between exposure to cadmium, lead, and mercury and the occurrence of urinary incontinence in women - Jinliang Ni; Ziye Li; Yi Lu; Houliang Zhang; Guangchun Wang; Jinbo Xie; Jun Xie; Yidi Wang; Yifan Zhang; Keyi Wang; Weipu Mao; Bo Peng (Environmental Science and Pollution Research, 2023)

Microplastic pollution destabilized the osmoregulatory metabolism but did not affect intestinal microbial biodiversity of earthworms in soil - Ronggui Tang; Minshen Ying; Yongming Luo; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Tao Sun; Yutao Cao; Zhihan Diao; Yuxin Zhang; Yichen Lian; Keyi Chen; Yan Yan; et al. (Environmental Pollution, 2023)

Impact of Titanium Dioxide-Graphene Oxide (TiO2-GO) Composite Nanoparticle on the Juveniles of the Giant River Prawn, Macrobrachium rosenbergii: Physio-Biochemistry and Transcriptional Response - Ziqi Guo; Jiabao Zuo; Jianbin Feng; Jiale Li; Shupeng Zhang; Keyi Ma (Marine Biotechnology, 2023)

Nanoplastics induce molecular toxicity in earthworm: Integrated multi-omics, morphological, and intestinal microorganism analyses - Ronggui Tang; Dong Zhu; Yongming Luo; Defu He; Haibo Zhang; Ali El-Naggar; Kumuduni Niroshika Palansooriya; Keyi Chen; Yan Yan; Xinghang Lu; Minshen Ying; Tao Sun; et al. (Journal of Hazardous Materials, 2023)

A synthesis of Carboniferous stratigraphy in Xinjiang, Northwest China with emphasis on regional and global correlations - Yong Tang; Xunyan Ye; Xiatian Wang; Xing Huang; Zhangshuai Hou; Keyi Hu; Sunrong Yang; Ying Li; Feifei Zhang; Shuzhong Shen; Xiangdong Wang (Journal of Asian Earth Sciences, 2023)

Potential of granular complexes of lime and montmorillonite for stabilizing soil cadmium and the underlying mechanisms - Gaoxiang Huang; Keyi Huang; Xingxiang Wang; Wuxing Shu; Wenjing Ren; Peng Wang; Hua Zhang; Minghua Nie; Mingjun Ding (Environmental Pollution, 2023)

Advances and future research in ecological stoichiometry under saline-alkali stress - Keyi Zhang; Lei Chang; Guanghui Li; Yuefen Li (Environmental Science and Pollution Research, 2023)

Effects of titanium dioxide (TiO2)/activated carbon (AC) nanoparticle on the growth and immunity of the giant freshwater prawn, Macrobrachium rosenbergii: potential toxicological risks to the aquatic crustaceans - Ziqi Guo; Jiabao Zuo; Xue Liu; Jinhua Gong; Keyi Ma; Jianbin Feng; Jiale Li; Shupeng Zhang; Gaofeng Qiu (Environmental Science and Pollution Research, 2022)

Effect of Bacteria in Algal Environment Regulated by Glucose Content on Ochromonas - Bo Zhang; Keyi Liu; Yanru Su; Anlong Zhang; Zhaojun Ji (BioEnergy Research, 2022)

Relationship between exposure to cadmium, lead, and mercury and the occurrence of urinary incontinence in women - Jinliang Ni; Ziye Li; Yi Lu; Houliang Zhang; Guangchun Wang; Jinbo Xie; Jun Xie; Yidi Wang; Yifan Zhang; Keyi Wang; Weipu Mao; Bo Peng (Environmental Science and Pollution Research, 2022)

Changes in plant inputs alter soil carbon and microbial communities in forest ecosystems - Jiguang Feng; Keyi He; Qiufang Zhang; Mengguang Han; Biao Zhu (Global Change Biology, 2022)
Global changes can alter plant inputs from both above‐ and belowground, which, thus, may differently affect soil carbon and microbial communities. However, the general patterns of how plant input changes affect them in forests remain unclear. By conducting a meta‐analysis of 3193 observations from 166 experiments worldwide, we found that alterations in aboveground litter and/or root inputs had profound effects on soil carbon and microbial communities in forest ecosystems. Litter addition stimulated soil organic carbon (SOC) pools and microbial biomass, whereas removal of litter, roots or both (no inputs) decreased them. The increased SOC under litter addition suggested that aboveground litter inputs benefit SOC sequestration despite accelerated decomposition. Unlike root removal, litter alterations and no inputs altered particulate organic carbon, whereas all detrital treatments did not significantly change mineral‐associated organic carbon. In addition, detrital treatments contrastingly altered soil microbial community, with litter addition or removal shifting it toward fungi, whereas root removal shifting it toward bacteria. Furthermore, the responses of soil carbon and microbial biomass to litter alterations positively correlated with litter input rate and total litter input, suggesting that litter input quantity is a critical controller of belowground processes. Taken together, these findings provide critical insights into understanding how altered plant productivity and allocation affects soil carbon cycling, microbial communities and functioning of forest ecosystems under global changes. Future studies can take full advantage of the existing plant detritus experiments and should focus on the relative roles of litter and roots in forming SOC and its fractions.

Microalgal–Bacterial Synergistic Interactions and Their Potential Influence in Wastewater Treatment: a Review - Atif Sial; Bo Zhang; Anlong Zhang; KeYi Liu; Syed Asad Imtiaz; Noman Yashir (BioEnergy Research, 2021)

Toonamicrocarpavarin, a new tirucallane-type triterpenoid from Toona Ciliata - Ling Zhang; Jianjun Xia; Yanqing Duan; Keyi Wei; Rui Gao; Dasan Li; Xiaomin Liu; Tiandong Zhang; Minghua Qiu (Natural Product Research, 2021)

Discrimination of Tourette Syndrome Based on the Spatial Patterns of the Resting–State EEG Network - Keyi Duan; Qian Wu; Yuanyuan Liao; Yajing Si; Joyce Chelangat Bore; Fali Li; Qin Tao; Li Lin; Wei Lei; Xudong Hu; Dezhong Yao; Changfu Pei; et al. (Brain Topography, 2021)

Bio-resolution of glycidyl (o, m, p)-methylphenyl ethers by Bacillus megaterium - Zhengfang Zhang; Yanming Sheng; Keyi Jiang; Zhao Wang; Yuguo Zheng; Qing Zhu (Biotechnology Letters, 2010)